Optimización de la calidad sensorial de una conserva de camarón (Litopenaeus vannamei) con tres tipos de acidulantes - Cedeño Segovia, Dayana Stefanía (2022)
The objective of this work was to establish the combination of acidulants that significantly optimize the texture and sensory quality of a shrimp conservation, in order to carry out the investigation, a Simplex-Latex mixture design was applied in which it was based on mixing the acid components citric (0.50 low, 2.50 high and the optimum 0.50) %, ascorbic (1.00 which is low, 3.00 which is high and 1.00 which is optimum) % and acetic (1.50 which is low, 3.00 which is high, and 3.50 which is the best). Ten treatments were produced with an experimental unit of 100g, which were replicated twice. Physicochemical analyzes (acidity and pH), texture, weight loss and sensory quality evaluated by 75 tasters were performed on shrimp conservation. a 7-point hedonic scale.